Economic Effects of Domestic and Neighbouring Countries` Cultural Diversity - Erkan Gören (University of Oldenburg, Department of Economics, 2013)
This paper investigates the economic growth impact of cultural diversity, both domestically and in neighbouring countries, in a balanced panel of 94 countries covering the period 1970 to 2004. The measures of cultural diversity used in this article were derived from a recently developed computer algorithm intended primarily to measure linguistic distances in an automated fashion. The empirical analysis suggests that the degree of cultural diversity in contiguous neighbouring countries has substantial positive effects on domestic per capita income growth, even controlling for a broad set of regional, institutional, religious and other proximate factors of economic growth. The conclusion is that culturally homogeneous countries gain a strategic advantage over their culturally diverse neighbours.
Keywords: O11; O5; 330; cultural diversity; ethnic diversity; economic growth; Wirtschaftswachstum; Interkulturelle Beziehungen; Kulturelle Identität; Schätzung; Welt